2018
DOI: 10.3389/fpsyg.2018.00814
|View full text |Cite
|
Sign up to set email alerts
|

How Can Prosocial Behavior Be Motivated? The Different Roles of Moral Judgment, Moral Elevation, and Moral Identity Among the Young Chinese

Abstract: Prior research has shown that moral judgment, moral elevation, and moral identity contribute to prosocial behavior. However, how these three motivating factors interact in predicting prosocial behaviors is not yet clear. The current study proposed and examined a moderated mediation model to illustrate the specific process of how prosocial behavior is motivated by these factors. A total of 264 Chinese undergraduate and graduate students participated in the present study (140 females; age range 17–26, M = 20.25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 54 publications
5
38
0
3
Order By: Relevance
“…It is also possible that norm transformations observed and reported in previous literature were caused by the activation of elevation [38]; this should be explicitly considered in future studies. Moreover, our findings agree with various other findings regarding moral elevation causing altruistic behavior [55,[61][62][63][64]. In short, the mere exposure to a cooperative environment involving CCs may directly cause some individuals to cooperate; meanwhile, other individuals are willing to mimic CCs' pro-social environment-related behaviors if their morals are elevated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is also possible that norm transformations observed and reported in previous literature were caused by the activation of elevation [38]; this should be explicitly considered in future studies. Moreover, our findings agree with various other findings regarding moral elevation causing altruistic behavior [55,[61][62][63][64]. In short, the mere exposure to a cooperative environment involving CCs may directly cause some individuals to cooperate; meanwhile, other individuals are willing to mimic CCs' pro-social environment-related behaviors if their morals are elevated.…”
Section: Discussionsupporting
confidence: 91%
“…Silvers and Haidt (2008) suggested that this experience of moral elevation is accompanied by the release in the body of oxytocin [55], a hormone that is associated with trust and pro-social behaviors [56][57][58][59][60]. Further, empirical experiments have found that this feeling of elevation can increase individuals' approval of pro-social behaviors, and further encourage them to engage in similar behaviors [55,56,[61][62][63][64]. Considering this, we hypothesize that moral elevation mediates the relationship between the existence of CCs and fellow members' cooperation in repeated public-goods dilemma games.…”
Section: Effect and Moral Elevationmentioning
confidence: 99%
“…Human values and moral norms are essential in creating the possibility that people obey behavioral demands and display prosocial behavior. There is evidence that values of self-transcendence and security (Bardi and Schwartz, 2003 ; Fischer and Smith, 2006 ; Sagiv et al, 2017 ; Schwartz et al, 2017 ; Wolf et al, 2020 ), as well as moral identity (including moral norms, thinking, and emotions) (Hardy et al, 2015 ; Ding et al, 2018 ; Patrick et al, 2018 ; Gotowiec and Mastrigt, 2019 ; Lebedeva, 2019 ) predict the prosocial behaviors (charity, voluntary assistance, cooperation, empathy).…”
Section: Introductionmentioning
confidence: 99%
“…Moral judgment refers to an evaluation or opinion regarding whether one’s behaviors are right or wrong according to ethical rules such as advocating for others’ well-being and prohibiting harming others (Heiphetz et al ., 2018), and thereby, such judgment is related to one’s humanity identification (Kahane et al ., 2015), prosocial behaviors (Ding et al ., 2018; Li et al ., 2018) and psychopathic status (Outhred et al ., 2016). Permissibility of moral judgment, an acceptability for transgression on ethical rules, is restrained by an emotional aversion to harmful actions (Gleichgerrcht et al ., 2013; McDonald et al ., 2017), such that people are less likely to endorse emotional harms as permissible, even if doing so would achieve a greater good (Greene et al ., 2001; Koenigs et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%